Low back pain during military service predicts low back pain later in life - Mattila, Ville M. (PLoS One, 2017)
The aim of the present study was to assess associations between physician diagnosed unspecified low back pain (LBP) during compulsory military service and self-reported LBP and physical fitness measured on average four years after military service. From a total of 1155 persons who had been pass medical examination for military service and who had completed physically demanding military training between 1997 and 2007, 778 men participated in a refresher military training course and physical tests. In this study, the association between LBP during military service and LBP in later life in addition to the association between LBP and physical fitness were examined. A total of 219 out of 778 participants (28%) had visited a physician due to some musculoskeletal symptom (ICD-10 M-diagnosis) during their military service. Seventy-four participants (9.5%) had visited a physician due to unspecified LBP during their service, and 41 (5.3%) had temporarily been absent from duty due to LBP. At the follow-up examination, 122 (15.7%) had reported LBP during the past month. LBP during military service was associated with self-reported LBP in the follow-up (p = 0.004). Of those who had been absent from duty due to LBP during their military service, 13 (31.7%) reported LBP during the past month. In risk factor analysis, no initial health behaviour and physical performance variables were associated with baseline LBP in the follow-up. The main finding of the present study was that unspecified LBP during military service predicts LBP in later life. On the basis of previous literature, it is also known that LBP is a common symptom and thus, one cannot expect to be symptomless the entire life. Interestingly, none of the health behaviours nor the physical performance studied in the follow-up were associated with baseline LBP. It appears that individuals prone to LBP have symptoms during physically demanding military service and also later in their life.